High-purity quartz sand and preparation method thereof

By heating and hydrolyzing silicon powder under alkaline conditions, combining ion exchange and multi-step drying treatment, high-purity quartz sand was successfully prepared, solving the problems of high-purity quartz sand in the prior art, which was high cost of preparation, low yield and difficult to remove impurities in the prior art. High purity and low cost quartz sand preparation are achieved.

CN119430204AActive Publication Date: 2025-02-14XIAN LANQIAO NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202510024671.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-02-14
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

It is difficult to efficiently prepare high-purity quartz sand in the prior art, especially products with purity of 4N8 and above, and the purification cost of natural ore is high, low yield, and impurities are difficult to remove.

Method used

Using water, mixed alkali and silicon powder as raw materials, silicon sludge is prepared by stirring, and then heated and hydrolyzed under alkaline conditions to obtain a sodium silicate solution, and impurities are removed through an ion exchange column, and finally by freezing, vacuum microwave drying and chlorination. Roasted to obtain high-purity quartz sand.

Benefits of technology

It has achieved the preparation of high-purity quartz sand, with a purity of 6N9, a uniform and controllable particle size, low cost, high yield, and high yield. It is suitable for high-tech industries such as photovoltaics and semiconductors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430204A_ABST
    Figure CN119430204A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of quartz sand preparation, and discloses high-purity quartz sand and a preparation method thereof. The method comprises the following steps: by taking water, mixed alkali and silicon powder as raw materials, uniformly stirring the silicon powder, the water and an additive to prepare silicon sludge, adding the rest raw materials into a reaction kettle, heating, then adding the silicon sludge into the reaction kettle in a frequency division manner, reacting to obtain a sodium silicate solution, removing anion and cation impurities, then adding an acid solution, heating to obtain silicic acid gel, and drying to obtain the silica gel. The silicic acid gel is subjected to freezing treatment, vacuum microwave drying and chloridizing roasting after unfreezing are conducted, and the high-purity quartz sand is obtained. According to the preparation method, the quartz sand with the purity higher than 99.9999% can be synthesized, the granularity of the quartz sand can be controlled according to the adding proportion of the acid solution, the content of gas-liquid inclusion in the quartz sand is remarkably reduced, and the quality of the quartz sand is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quartz sand preparation, and relates to high-purity quartz sand and a preparation method thereof. Background Art

[0002] High purity quartz sand is a kind of SiO 2 Non-metallic mineral raw materials with a content of more than 99.95% have excellent physical and chemical properties, such as high temperature resistance, corrosion resistance, low thermal expansion, high insulation and light transmittance. The demand for high-purity quartz sand in the photovoltaic and semiconductor fields is growing rapidly, especially for products with a purity of 4N5 or above. Semiconductor products have high purity requirements and usually require quartz sand with a purity of 4N8 or above. In the photovoltaic industry, high-purity quartz sand, as a raw material for the manufacture of quartz crucibles, provides important support for the production of monocrystalline silicon, and its demand continues to grow with the increase in new photovoltaic installed capacity.

[0003] At present, the main source of quartz sand on the market is natural ore purification. Due to the complex composition and structure of the ore, it is difficult to purify ordinary quartz ore to more than 99.99%. High-purity quartz sand can only be purified from clean natural crystals produced by a few mineral veins. However, the resources of such mineral veins are limited, which limits the output of ultra-high purity quartz sand. Quartz sand on the market often contains impurity ions such as Al, Ti, and Fe. These ions exist in the quartz lattice in the form of isomorphism and are difficult to completely remove by physical methods. At the same time, gas-liquid inclusions are also common impurity forms in quartz. They have a significant impact on the purity of quartz sand and are difficult to remove.

[0004] Therefore, it is of great significance to explore a method for synthesizing high-purity quartz sand to solve the problems of high cost and low yield of quartz sand prepared by purifying natural crystals in the current market, and the difficulty in removing impurities and gas-liquid inclusions. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a high-purity quartz sand and a preparation method thereof. The method uses water, mixed alkali and silicon powder as raw materials, mixes silicon powder and water in a mass ratio of 1:0.6~1.6 on the basis of the raw material ratio, adds additives and stirs evenly to prepare silicon mud, adds the remaining water and mixed alkali in the raw materials into a reactor and heats, then adds the silicon mud into the reactor in multiple times, reacts to obtain a sodium silicate solution, removes anions and cations from the sodium silicate solution, adds an acid solution, heats to obtain a silica gel, centrifuges the silica gel and freezes it, thaws it, vacuum microwaves it, and chlorinates it to obtain high-purity quartz sand. The purity of the quartz sand synthesized by the present invention reaches 6N9 level, and the particle size is uniform and controllable. The present invention provides a method for preparing high-purity quartz sand with low cost, high output and high yield for photovoltaic, semiconductor and other fields.

[0006] To achieve the technical purpose of the present invention, on the one hand, the present invention provides a high-purity quartz sand and a preparation method thereof, which specifically comprises the following steps: S1: Weigh water, mixed alkali and silicon powder in a mass ratio of 17~25:1:0.7~1.4 to obtain the total raw material, weigh 1~5wt% of LQ-TJ69 additive of the total raw material, and based on the total raw material ratio, mix silicon powder and water in a mass ratio of 1:0.6~1.6, add LQ-TJ69 additive and mix evenly to prepare silicon mud.

[0007] S2: Add the remaining water and mixed alkali in the total raw materials into the reactor and heat with stirring. When the temperature of the reactor reaches the reaction temperature range of 60-80°C, add the silicon mud into the reactor in batches, wait for the reaction and slowly add the next batch until all the silicon mud is added. Stir and continue heating from the beginning to the end of the reaction for 4-8 hours. When no bubbles are released during the reaction, introduce nitrogen for 40-60 minutes, and perform ultrasonic treatment at the same time. The ultrasonic power is 600W and the ultrasonic frequency is 40kHz. Then filter to obtain a high-purity sodium silicate solution.

[0008] S3: 0.5~3wt% of LQ-FS69 dispersant of the total raw materials is added to the sodium silicate solution obtained in S2 and stirred evenly, and then passed through a continuous series ion exchange column to first remove inorganic impurities, and then passed through an ion exchange column to remove alkali metal impurities.

[0009] S4: Mix the mixed acid and water in a mass ratio of 1:10-14 to obtain a mixed acid solution, and pour the mixed acid solution into the sodium silicate solution in S3 that passes through the continuous series ion exchange column, stirring continuously during the pouring process, and stopping stirring after all the mixed acid solution is poured in. The mass ratio of the sodium silicate solution, acid and water is 8.5-10.5:1:10-14. Heat the solution to 60-85°C, and obtain silicic acid gel after heating for 2-5 hours.

[0010] S5: Place the silica gel in a vacuum refrigerated centrifuge for freeze-thaw treatment. Centrifuge at 1600~2000rpm for 20~30min to remove the water in the silica gel, then freeze for 10~24h at a freezing temperature of -20~-13℃, a rotation speed of 500~800rpm, and a vacuum degree of -0.06~-0.1pa, then thaw and centrifuge at 1600~2000rpm for 30~40min to remove the water produced by thawing. Place in a microwave vacuum drying oven with a vacuum degree of -0.1pa, a microwave power of 0.7kW, and a temperature of 100~180℃, and dry for 5~15h to form particles. Then sieve to remove quartz sand particles larger than 100μm and smaller than 50μm.

[0011] S6: The screened quartz sand particles are subjected to chlorination roasting at a temperature range of 800-1000°C for a time of 4-8 hours. After roasting, magnetic separation is performed to obtain quartz sand particles with high purity, few inclusions, and uniform and controllable particle size.

[0012] Specifically, the LQ-TJ69 additive is used to increase the reaction rate, and the LQ-FS69 dispersant is used to increase the fluidity of the solution. The addition of the LQ-TJ69 additive and the LQ-FS69 dispersant of the present invention can significantly promote the reaction. After adding the LQ-TJ69 additive, the reaction time in the reactor can be significantly reduced, and the proportion of residues in the reactor is significantly reduced, indicating that the addition of the LQ-TJ69 additive can significantly promote the hydrolysis reaction of silicon mud under alkaline conditions, the substrate silicon powder is completely converted into sodium silicate, and the reaction is more thorough.

[0013] Specifically, the mixed alkali in S1 is composed of sodium hydroxide, potassium hydroxide and tetramethylammonium hydroxide, and the mass ratio is 0.8~1.2:0.8~1.2:0.2~0.5. Sodium hydroxide and potassium hydroxide have strong alkalinity and can promote the rapid occurrence of the initial reaction. Tetramethylammonium hydroxide helps to reduce the surface tension of water and can accelerate the reaction process. The ultrasound in S2 uses a probe-type ultrasonic instrument to remove oxygen from the system. The mixed acid in S4 is composed of hydrochloric acid and acetic acid in a volume ratio of 3:1. The chlorination roasting described in S6 uses hydrogen chloride gas.

[0014] Specifically, the present invention does not specifically limit the ion exchange column for removing inorganic impurities and alkali metal impurities in S3, and those skilled in the art can select the specific type of ion exchange column according to the type of impurities.

[0015] Specifically, the equipment for containing quartz sand in S1, S2, S4, and S5 is made of PTFE or PP material to avoid the introduction of other impurities, and the container used for chlorination roasting is a quartz crucible.

[0016] On the other hand, the present invention claims protection for a high-purity quartz sand obtained by the above-mentioned high-purity quartz sand preparation method. The high-purity quartz sand prepared by the present invention is 6N9 grade, with a purity of more than 99.9999%, and can also significantly reduce the content of gas-liquid inclusions in the quartz sand, thereby improving the quality of the quartz sand. The quartz sand prepared by the present invention has a high yield rate, which is more than 80%. The quartz sand prepared by the present invention has broad application prospects in high-tech industries such as electronic information, optical fiber, and photovoltaic industries.

[0017] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages: (1) The quartz sand preparation method of the present invention can obtain quartz sand particles with high purity, few inclusions and uniform particle size. The quartz sand prepared by the present invention using industrial-grade silicon powder as raw material has a purity of 6N9 level and an average particle size of 62.5~72.3μm, which is significantly improved compared with the quartz sand of the prior art, which can only reach the 4N9 level. The preparation method of the present invention can significantly reduce the content of gas-liquid inclusions in quartz sand and improve the quality of quartz sand. The quartz sand prepared by the present invention has broad application prospects in high-tech industries such as electronic information, optical fiber, and photovoltaic industries. The process path provided by the present invention can be scaled up and industrialized, and has the advantages of high yield, excellent product quality, low energy consumption, and low cost. The quartz sand yield of the preparation method provided by the present invention is above 85%, and the output rate is above 94%.

[0018] (2) The present invention changes the state of the raw material silicon powder, combines the silicon powder with water and LQTJ-69 additive in a certain proportion to obtain silicon mud, so that the hydrolysis reaction of the silicon powder under alkaline conditions occurs more rapidly and the reaction is more thorough. The present invention has found through experiments that adding LQ-TJ69 additive and preparing silicon powder into silicon mud can significantly reduce the reaction time in the reactor, and the proportion of residues in the reactor is significantly reduced, indicating that the technical solution can significantly promote the hydrolysis reaction of silicon mud under alkaline conditions, the substrate silicon powder is completely converted into sodium silicate, and the reaction is more thorough.

[0019] (3) The present invention can control the particle size of quartz sand by adjusting the concentration of the acid solution. The concentration of the acid solution has a great influence on the particle morphology and particle size of the quartz sand, which further affects the particle morphology and particle size of the synthetic quartz sand by directly affecting the acid environment of the reaction system. The present invention has found through experiments that the quartz sand particles prepared by the mixed acid solution with a mass ratio of acid to water of 1:12 have a concentrated particle size, a small range, a particle size that better meets the requirements of practical applications, and a smaller inclusion content in the quartz sand.

[0020] (4) The present invention uses a combination of frozen centrifugation, freeze-thaw and vacuum microwave drying to dry the quartz sand particles, which reduces the appearance of inclusions during the synthesis process. The surface of the obtained quartz sand is smoother. Compared with conventional drying methods, energy consumption and construction period are greatly shortened. Compared with the scheme of directly drying the gel or freezing the gel and then drying it in an oven, the quartz sand particles obtained by the process of the present invention are smaller in size and more uniform in particle size, and the yield of quartz sand can be significantly improved.

[0021] (5) The present invention uses a mixed alkali obtained by mixing sodium hydroxide, potassium hydroxide and tetramethylammonium hydroxide as one of the raw materials. Sodium hydroxide and potassium hydroxide have strong alkalinity and can promote the rapid occurrence of the initial reaction. Tetramethylammonium hydroxide helps to reduce the surface tension of water and can accelerate the reaction process. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Microscope image of the quartz sand prepared for Experiment 1.

[0023] Figure 2 Microscope image of the quartz sand prepared for Experiment 2.

[0024] Figure 3 Scanning electron micrograph of the quartz sand prepared for Experiment 1.

[0025] Figure 4 Scanning electron micrograph of the quartz sand prepared for Experiment 2. DETAILED DESCRIPTION

[0026] The technical scheme of the present invention is now described in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.

[0027] The silicon powder used in the present invention is industrial-grade silicon powder, the pure water is industrial pure water, and the reagents are all chemically pure.

[0028] LQ-TJ69 additive and LQ-FS69 dispersant are provided by Xi'an Blue Bridge New Energy Technology Co., Ltd. The active ingredient of LQ-TJ69 additive is N , N -dimethylacetamide, pyridine, and tert-butylamine, and the effective ingredients account for 1%, 1%, and 2% of the total volume respectively, and water is used as the solvent; the effective ingredients of LQ-FS69 dispersant are composed of anhydrous ethanol and methylpentanol, and the effective ingredients account for 3.2% and 0.8% of the total volume respectively, and water is used as the solvent.

[0029] Example 1 This embodiment provides a method for preparing high-purity quartz sand, which specifically includes the following steps: S1: The total raw material is weighed according to the mass ratio of pure water: mixed alkali: silicon powder = 17~25:1:0.7~1.4, and 1~5wt% of the total raw material LQ-TJ69 additive is weighed. The mixed alkali is composed of sodium hydroxide, potassium hydroxide and tetramethylammonium hydroxide, and the mass ratio is 0.8~1.2:0.8~1.2:0.2~0.5. Under the premise of the total raw material ratio, silicon powder and pure water are mixed at a mass ratio of 1:0.6~1.6, and then LQ-TJ69 additive is added to prepare silicon mud.

[0030] S2: Add the remaining pure water and mixed alkali in the total raw materials into the reactor and heat with stirring. When the temperature of the reactor reaches the reaction temperature range of 60-80°C, slowly add the silicon mud into the reactor in batches. Wait for the reaction to slow down (fewer bubbles are generated) and then add the next batch until all the silicon mud is added. The reaction lasts for 4-8 hours from the beginning of heating to the end of the reaction. When no bubbles are released during the reaction, introduce nitrogen for 40-60 minutes and perform ultrasonic treatment at the same time. The ultrasonic power is 600W and the ultrasonic frequency is 40kHz. The ultrasound uses a probe-type ultrasonic instrument to remove oxygen in the system, and then filter to obtain a high-purity sodium silicate solution.

[0031] S3: Add 0.5~3wt% of LQ-FS69 dispersant of the total raw materials to the sodium silicate solution obtained in S2 and stir evenly, then pass through a continuous series ion exchange column to first remove trace and various inorganic impurities and some alkali metal ions (the model of the ion exchange resin is Kohis T-42), and then pass through an ion exchange column for removing alkali metal impurities (the model of the ion exchange resin is Xi'an Lanxiao LHSI-10).

[0032] S4: Mix a mixed acid (hydrochloric acid and acetic acid in a volume ratio of 3:1) and water in a mass ratio of 1:10-14 to obtain a mixed acid solution, and pour the mixed acid solution into the sodium silicate solution in S3 that has passed through an ion exchange column, stirring continuously during the pouring process, and stopping stirring after all the mixed acid solution has been poured in. The mass ratio of the sodium silicate solution, the mixed acid and water is 8.5-10.5:1:10-14. Heat the solution to 60-85°C, and obtain a silica gel after heating for 2-5 hours.

[0033] S5: Place the silica gel in a vacuum refrigerated centrifuge, centrifuge at 1600~2000rpm for 20~30min to remove the water in the silica gel, then freeze for 10~24h at a freezing temperature of -20~-13℃, a rotation speed of 500~800rpm, and a vacuum degree of -0.06~-0.1pa, then thaw and centrifuge at 1600~2000rpm for 30~40min to remove the water produced by thawing. Place in a microwave vacuum drying oven with a vacuum degree of -0.1pa, a microwave power of 0.7kW, and a temperature of 100~180℃, and dry for 5~10h to form particles. Then sieve to remove quartz sand particles larger than 100μm and smaller than 50μm.

[0034] S6: The screened quartz sand particles are subjected to chlorination roasting (using hydrogen chloride gas) at a roasting temperature range of 800-1000°C for 4-8 hours. After roasting, magnetic separation is performed to obtain quartz sand particles with high purity, few inclusions and uniform particle size.

[0035] In this embodiment, a total of 3 groups of tests and 3 groups of comparative tests were carried out. The test parameters of tests 1 to 3 and comparative tests 1 to 3 are shown in Table 1. The test parameters of comparative test 1 are the same as those of test 1, with the following differences: no LQ-TJ69 additive and no LQ-FS69 dispersant were added, the silicon powder and pure water in the total raw materials were not prepared into silicon mud in S1, and the silicon powder was directly added to the reactor in batches in S2. The test parameters of comparative test 2 are the same as those of test 1, with the following differences: the silica gel obtained in S4 was frozen at -20°C and then dried in an ordinary oven. In comparative test 3, quartz sand was prepared with reference to the technical scheme of implementation example 3 in the patent with application number 202110866870.7. The parameters of the quartz sand obtained in each test are shown in Table 2, the ICP impurity concentration test results of the quartz sand obtained in each test are shown in Table 3, and the microscope image of the quartz sand prepared in test 1 is shown in Table 3. Figure 1 As shown, the microscope image of the quartz sand prepared in Experiment 2 is as follows Figure 2 As shown, the scanning electron microscope image of the quartz sand prepared in Experiment 1 is as follows Figure 3 The scanning electron microscope image of the quartz sand prepared in Experiment 2 is shown in Figure 4 shown.

[0036] Table 1: Experimental parameters for preparation of high purity quartz sand

[0037]

[0038] Table 2: Parameters of quartz sand prepared in Experiments 1 to 3 and Comparative Experiments 1 to 3

[0039] Note: The output rate is the ratio of the actual output sample mass to the theoretical output; the finished product rate is the ratio of the qualified mesh sample mass to the total sample mass.

[0040] Table 3: ICP impurity concentration test results of quartz sand prepared in Experiments 1 to 3 and Comparative Experiments 1 to 3

[0041] Depend on Figure 1~Figure 4 It can be seen that the quartz sand particles prepared by the present invention have a smooth surface without holes, few inclusions and uniform particle size.

[0042] As shown in Table 2, the concentration of the mixed acid solution has a great influence on the particle size range of the quartz sand. When the mass ratio of the mixed acid to water is in the range of 1:10 to 14, the more water is added, the larger the particle size of the quartz sand. The mixed acid solution further affects the particle morphology and particle size of the synthetic quartz sand by affecting the acidity environment of the reaction system. In particular, the quartz sand particles prepared by the mixed acid solution with a mass ratio of the mixed acid to water of 1:12 have a concentrated particle size, a small range, and a particle size that is more in line with the actual application requirements, and the inclusion content in the quartz sand is less.

[0043] As can be seen from Table 2, adding LQ-TJ69 additive and LQ-FS69 dispersant, as well as mixing silicon powder with water and LQ-TJ69 additive to prepare silicon mud can significantly reduce the reaction time in the reactor, and the proportion of residues in the reactor is significantly reduced, indicating that the addition of LQ-TJ69 additive can significantly promote the hydrolysis reaction of silicon mud under alkaline conditions, the substrate silicon powder is completely converted into sodium silicate, and the reaction is more thorough.

[0044] As can be seen from Table 2, the present invention first removes the moisture in the silica gel, then freezes it, continues to centrifuge to remove the moisture generated by thawing after thawing, and puts it into a microwave vacuum drying oven to dry to obtain quartz sand particles. This technical solution can significantly reduce the content of gas-liquid inclusions in the quartz sand, and the quartz sand has a smaller particle size and a uniform particle size distribution, and can also significantly improve the yield of quartz sand.

[0045] It can be seen from Tables 2 and 3 that within the parameter range of the quartz sand preparation method provided by the present invention, quartz sand particles with high purity, few inclusions and uniform particle size can be obtained, and the purity of the quartz sand particles reaches 6N9 level, and the average particle size is 62.5~72.3μm. Compared with the quartz sand in the prior art, which can only reach 4N9 level, the purity has been significantly improved.

[0046] The above embodiments and descriptions are merely descriptions of preferred implementations of the present invention. The present invention is not limited by the above embodiments. Without departing from the spirit and scope of the present invention, various changes and improvements made to the technical solutions of the present invention by ordinary technicians in this field should fall within the protection scope determined by the present invention.

Claims

1. A method for preparing high-purity quartz sand, characterized in that: include: Raw materials, the raw materials are water, mixed alkali and silicon powder; The mixed alkali is composed of sodium hydroxide, potassium hydroxide and tetramethylammonium hydroxide; The raw materials and additives are subjected to heating reaction to obtain a sodium silicate solution, anionic and cationic impurities are removed, a mixed acid solution is added, and the mixture is heated to obtain a silicate gel; The silica gel is subjected to freezing, thawing, vacuum microwave drying, and then chlorination roasting to obtain quartz sand particles.

2. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The heating reaction comprises: mixing part of the water in the raw material with the silicon powder and the additive to form silicon mud, heating the remaining water and the alkali, and adding the silicon mud in batches after reaching the reaction temperature of the heating reaction; In the silicon mud, the mass ratio of silicon powder to water is 1:0.6~1.6; The additive is added in an amount of 1-5% of the mass of the raw material.

3. The method for preparing high-purity quartz sand according to claim 2, characterized in that: In the raw materials, the mass ratio of water, mixed alkali and silicon powder is 17-25:1:0.7-1.4; In the mixed alkali, the mass ratio of sodium hydroxide, potassium hydroxide and tetramethylammonium hydroxide is 0.8-1.2:0.8-1.2:0.2-0.

5.

4. The method for preparing high-purity quartz sand according to claim 2, characterized in that: The reaction temperature of the heating reaction is 60-80° C., and the total reaction time of the heating reaction and the heating treatment is 4-8 hours; After the heating reaction is completed, nitrogen is introduced for 40 to 60 minutes, and ultrasonic treatment is performed at the same time; The power of the ultrasonic treatment is 600 W, and the frequency of the ultrasonic treatment is 40 kHz.

5. The method for preparing high-purity quartz sand according to claim 1, characterized in that: Before removing the anionic and cationic impurities, a dispersant is added to the sodium silicate solution, and the amount of the dispersant added is 0.5-3% of the mass of the raw material.

6. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The mixed acid solution is composed of mixed acid and water, and the mass ratio of the mixed acid to water in the mixed acid solution is 1:10-14; The mixed acid consists of hydrochloric acid and acetic acid, and the volume ratio of hydrochloric acid to acetic acid is 3:1; The mass ratio of the sodium silicate solution to the mixed acid solution is 8.5-10.5:

1.

7. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The heating temperature is 60-85°C, and the heating time is 2-5h; The temperature of the vacuum microwave drying is 100-180° C., the time of the vacuum microwave drying is 5-10 h, the vacuum degree of the vacuum microwave drying is -0.1 Pa, and the microwave power of the vacuum microwave drying is 0.7 kW.

8. The method for preparing high-purity quartz sand according to claim 1, characterized in that: Before freezing, the silica gel is centrifuged at 1600-2000 rpm for 20-30 min; The freezing temperature is -20 to -13°C, the freezing time is 10 to 24 hours, and the centrifugal speed during the freezing process is 500 to 800 rpm; After thawing, centrifuge at 1600-2000 rpm for 30-40 min; The freezing and thawing are carried out under a vacuum condition of -0.06~-0.1 Pa.

9. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The temperature of the chlorination roasting is 800-1000°C, and the time of the chlorination roasting is 4-8h; The chlorination roasting uses hydrogen chloride gas.

10. A high-purity quartz sand, characterized in that: The high-purity quartz sand is prepared by the preparation method of high-purity quartz sand according to any one of claims 1 to 9, wherein the purity of the high-purity quartz sand is higher than 99.9999%.

Citation Information

Patent Citations

  • Method for preparing silica sol

    CN102101674A

  • Colloidal titanium dioxide sols

    CN104761931A

  • Preparation method of silica sol controllable in grain size

    CN105731468A

  • Purification method of high-purity quartz sand with SiO2 purity more than or equal to 99.99%

    CN110127708A

  • Preparation method of silicon oxide nanoparticles with uniform particle sizes

    CN112978737A

Cited By

  • Preparation method of quartz sand

    CN121377048A

  • Preparation method of spherical silica powder

    CN121849987A

  • A method for preparing spherical silicon fine powder

    CN121849987B